An in-Depth Translation Assessment on Subtitling Strategies in Documentary Youtube Captions - Baharuddin, Baharuddin; Putera, Lalu Jaswadi; Wardana, Lalu Ali; Herayana, Desi; Pramestya, I Gusti Agung Ayu Sasmitha Dewi Anggita; Camila, Alia Fitrida; Rahma, Auliya; Sazwan, M.; Wulandary, Duwi (Journal of Languages and Language Teaching, 2025)
Subtitling has become a vital tool for disseminating ideas and information through online video. This study takes a deep dive into the translation strategies employed in the subtitling of the acclaimed Netflix documentary series â€œOur Planet.â€ Drawing on Gottlieb's established theory of translation techniques for subtitling, this research analyses the subtitling approaches within the episodes of the series. The findings reveal that the transfer strategy presenting direct lexical translation is the dominant approach (71%) used by subtitlers. However, the analysis also uncovers nuanced applications of other strategies, such as expansion, paraphrasing, and condensation, which work in tandem to enhance the clarity and naturalness of the target language subtitles. By examining this rich dataset of documentary video subtitles, this study provides valuable insights into the complex decision-making processes of professional subtitlers especially those that is related to cross-cultural comprehensio. The results suggest that while transfer is the primary technique, subtitlers thoughtfully employ a mix of strategies to deliver an optimal viewing experience to multilingual audiences. This study offers a groundbreaking exploration of the intricacies involved in translating educational and informative video content for global distribution.